Performance of composites versus metals under extreme loading. Issue 1 (March 2017) - Szuladziński, Gregory
Most structures, including airframes, are designed using quasi-static criteria. With this approach, composites are superior to metals, as they are stronger and have a smaller mass density. This article addresses a question of the remaining margins of safety when the loads are outside the design envelope, be they in magnitude or in character. The answers are provided first for some simple panels, and then for a selected airliner wing. In each case, the items compared are designed using the same design load. A related problem of dynamic buckling is addressed in detail and it is explained how it may lead to great destructive power of slender structural elements. The difference in performance between metals and composites, in that regard, is addressed. A few numerical examples and simulation results are provided.